An effective start-up of thermophilic UASB reactor by seeding mesophilically-grown granular sludge - Syutsubo, Kazuaki; Harada, Hideki; Ohashi, Akiyoshi; Suzuki, Hiroshi (Water science and technology, 1997)
After seeded with mesophilically-grown (35°C) granular sludge, a laboratory-scale UASB reactor was thermophilically (55°C) operated over 8 months by feeding with an alcohol distillery wastewater. Use of mesophilically-grown granules as a seed material proved to be more advantageous for rapid and stable start-up of thermophilic UASB process, compared with the use of suspended-growth sludge taken from a thermophilic anaerobic digester. The reactor accommodated successfully a COD loading 30 kgCOD·m−3·d−1 , with a COD removal efficiency of 85%. However, during a period of 30 kgCOD·m−3·d−1 , propionate accumulated in the effluent up to 300–600 mgCOD·l−1. Thermophilic cultivation caused a drastic increase of methanogenic activities (55°C) of the retained sludge: 4.4 times for acetate, 4.6 times for propionate, and 3.5 times for hydrogen as large as those of the seed sludge. A considerably low value of propionate-fed methanogenic activity, i.e. only 1/5 of acetate-fed activity and only 1/23 of hydrogen-fed activity, suggested that the propionate degradation is subject to be a rate-limiting step in thermophilic anaerobic processes.